A survey on automated melanoma detection. (August 2018) - Okur, Erdem; Turkan, Mehmet
Abstract: Skin cancer is defined as the rapid growth of skin cells due to DNA damage that cannot be repaired. Melanoma is one of the deadliest types of skin cancer, which originates from melanocytes. While other skin cancer types have limited spreading capabilities, the danger of melanoma comes from its ability to spread (metastasize) rapidly. Fortunately, it can be detected by visual inspection of the skin surface, and it is 100% curable if identified in the early stages. However, detection by "subjective visual inspection" creates an important problem, due to investigators' different levels of experiences and education. Dermoscopy (dermatoscopy) has significantly increased the diagnostic accuracy of melanoma since late 90's. In addition, several systems have been proposed in order to assist investigators or to perform an automatic melanoma detection. This survey focuses on the algorithms for automated melanoma detection in dermoscopic images through an extensive analysis of the stages in methodologies proposed in the literature, and by examining related concepts and describing possible future directions through open problems in this domain of research. Highlights: A survey pointing out the high importance of melanoma and its automatic detection. Covers wide range of methodologies and current state-of-the-art advancements. Supported with clinical feature observations by dermatologists. Provides suggestions for successful future research directions.